Marés e correntes na otimização de manobras de navios na baía de são marcos, São Luís – MA - MAGALHÃES, Augusto César Rodrigues (2018)
In the constant pursuit of productivity gains in the safe and sustainable port operation, this work aims to give visibility to the gains of the vessel maneuvers by optimizing the mooring times of the Ponta da Madeira Maritime Terminal (TMPM). For the case study, the optimization of the maneuvers of Terminal Marítimo of Ponta da Madeira - TMPM, which is the largest volume handling terminal of iron ore in Brazil. With data collection of speed and direction of current in a certain period of time it was possible to better understand the dynamics of the movement of the currents that influence in the ship’s maneuvers, making possible the search for magnification of the maneuver windows, reducing free time without productivity